Seasonality and Reproductive Aspects of Amphibian Anurans in a Rainforest Fragment in Pernambuco, Brazil - Santos, Ednilza Maranhão dos; Vasconcelos, Simão Dias (Revista Nordestina de Zoologia, 2012)
Temporary ponds can harbor a wide diversity of anuran species, which may exhibit marked differences in seasonal occupation and reproductive modes. This study was carried out in a temporary pond located at the Estação Ecológica of Tapacurá, Pernambuco, Northeastern Brazil. Nocturnal and diurnal observations were carried out monthly between September/1999 and August/2000. There was a temporal organization to 25 species, distributed between six families: Bufonidae (1), Hylidae (13), Leptodactylidae (6), Leuperidade (2), Microhylidae (2) and Ranidae (1). The highest species richness (n = 17) in reproductive activity was observed during the rainy season. (n = 17 species). Vocalization activity was seasonal and varied according to the species. Five reproductive modes were registered in the pond during the study.